PENGARUH LIKUIDITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Siskawati, Siskawati; Triani, Neks; Ilham, Surianto (Jurnal Akuntansi Kompetif, 2025)
This research is conducted to explore how liquidity and profitability influence the stock values of transportation sector firms listed on the Indonesia Stock Exchange. Employing a quantitative approach, the study gathers data through a documentation method by analyzing financial statements available on the official IDX website (www.idx.co.id). The research population includes all transportation firms recorded on the IDX from 2020 to 2023, with a purposive sampling technique selecting 17 companies as the research sample. The findings reveal that both liquidity and profitability exert a significantly positive impact on stock values. These results highlight that liquidity and profitability serve as crucial determinants in shaping stock price movements within corporate entities.Keywords: Liquidity, Profitability, Stock Prices